Insights into cavitation enhancement: Numerical simulation and spectrum analysis of a novel dual-frequency octagonal ultrasonic reactor - Zhiping Shi; Zedong Wang; Bowen Yang; Liyan Liu (Ultrasonics Sonochemistry)
Ultrasonic reactors, widely applied in process intensification, face limitations in their industrial application due to a lack of theoretical support for their structural design and optimization, particularly concerning the uniformity of the cavitation zone. Addressing this gap, our study introduces a novel approach to design a multi-frequency octagonal ultrasonic reactor of capacity 9.5 L through numerical simulation and spectrum analysis. The effects of reactor shape, transducer position, and multi-frequency ultrasound interaction on the sound pressure distribution in the reactor were simulated, employing a linear wave equation that accounts for the inhomogeneous distribution of bubbles. The accuracy of sound pressure amplitude predictions has been validated through a multi-frequency simulation method, exhibiting good consistency with experimental data. The results revealed that an octagonal structure with transducers positioned at the bottom and sides enhances the uniformity and distribution of the cavitation area compared to traditional rectangular designs. Notably, the combination of 20 and 40 kHz frequencies at a driving pressure of 3 bar significantly enhances cavitation rates to 69.2 %, surpassing the single frequency of 40 kHz by an increase of 16.5 %. The enhanced cavitation rate can be attributed to the dual-frequency operation, which facilitates larger bubble radii, along with higher collapse temperatures and pressures, as determined through bubble dynamics calculations. Moreover, spectrum analysis method enables energy separation, showing that the introduction of a 40 kHz transducer into a 20 kHz field markedly strengthens both steady and transient cavitation intensities. These findings offer practical insights for their structural design and optimization, paving the way for their broader industrial application.